O pioneers! (Great Plains Trilogy, ,, 2009)
Alexandra, daughter of a Swedish immigrant farmer in Nebraska, inherits the family farm and finds love with an old friend.

My Antonia (Prairie Trilogy, ,, 1994)
"Set in Nebraska in the late 19th century, this tale of the spirited daughter of a Bohemian immigrant family planning to farm on the untamed land comes to us through the romantic eyes of Jim Burden. He is, at the time of their meeting, newly orphaned and arriving at his grandparents' neighboring farm on the same night her family strikes out to make good in their new country." --

Love comes softly (Love comes softly series, 1, 1, 2019)
"Nineteen-year-old Marty Claridge starts west with her adventurous, boyish husband, Clem, seeking to claim land and hoping for good fortune. But when the venture turns suddenly to tragedy, Marty is left alone with her great loss. And coupled with her grief and heartache is the grim reality that there is no way to return home. Clark Davis and his little girl, Missie, are also in great need. Clark's wife has died, leaving him to care to Missie and the farm at the same time. His offer to Marty comes with good intention, but will courage and faith be enough to bring them to true love?"--from Goodreads.com.

Lone women: a novel (Thorndike Press large print Black voices, ,, 2023)
"Adelaide Henry carries an enormous steamer trunk with her wherever she goes. It's locked at all times. Because when the trunk opens, people around Adelaide start to disappear. The year is 1915, and Adelaide is in trouble. Her secret sin killed her parents, forcing her to flee California in a hellfire rush and make her way to Montana as a homesteader. Dragging the trunk with her at every stop, she will become one of the "lone women" taking advantage of the government's offer of free land for those who can tame it--except that Adelaide isn't alone. And the secret she's tried so desperately to lock away might be the only thing that will help her survive the harsh territory. Crafted by a modern master of magical suspense, Lone Women blends shimmering prose, an unforgettable cast of adventurers who find horror and sisterhood in a brutal landscape, and a portrait of early-twentieth-century America like you've never seen. And at its heart is the gripping story of a woman desperate to bury her past--or redeem it"--

Woman of sunlight (Brides of Hope Mountain, 2, 1, 2020)
After years of isolation on top of Hope Mountain, Ilsa Nordegren and her sisters provide refuge for members of the Warden family, who have escaped from a land-grabbing cattle baron. The last thing Mitch Warden expects is to be smitten with Ilsa, a strong-willed, dark-haired woman who dresses like Robin Hood and defends herself better than most men. Mitch vows to help his family reclaim their land, but first he must draw away the hired killers who are tracking him. That means a journey to the city -- and when Ilsa insists on joining him, the mismatched apir suddenly find themselves on an adventure they'll never forget.

Aiming for love (Brides of Hope Mountain, 1, 1, 2019)
Josephine Nordegren is one of three sisters who grew up nearly wild in southwestern Colorado. She has the archery skills of Robin Hood and the curiosity of the Little Mermaid, fascinated by but locked away from the forbidden outside world--a world she's been raised to believe killed her parents. When David Warden, a rancher, brings in a herd much too close to the girls' secret home, her older sister especially is frightened, but Jo is too interested to stay away. David's parents follow soon on his heels, escaping bandits at their ranch. David's father is wounded and needs shelter. Josephine and her sisters have the only cabin on the mountain. Do they risk stepping into the world to help those in need? Or do they remain separated but safe in the peaks of Hope Mountain?